Early indication of noise-induced hearing loss from PMP use in adolescents: A cross-sectional analysis - Diana C Colon; Ulla Verdugo-Raab; Carmelo P Alvarez; Thomas Steffens; Steven C Marcrum; Stefanie Kolb; Caroline Herr; Dorothee Twardella (Noise and Health, 2016)
Context: Distortion product otoacoustic emissions (DPOAEs) may indicate preclinical noise-induced hearing loss (NIHL) in adolescents from unsafe personal music player (PMP) use. Aims: The objective, therefore, was to observe preclinical signs of NIHL in 9th grade adolescents with clinically normal hearing by comparing DPOAE signals between different levels of A-weighted equivalent PMP exposure. Settings and Design: Subjects were recruited from all secondary-level schools located in the city of Regensburg, Germany during two academic years 2009/2010 and 2010/2011. Subjects and Methods: A-weighted equivalent sound pressure levels (SPLs) for a 40-hour work week (LAeq,40h) were estimated from questionnaire responses on output and duration of PMP use of the previous week. Subjects were then categorized into four levels of exposure: <80, 80–85, >85 to <90, and ≥90 A-weighted Decibel [dB(A)]. DPOAE signals were collected by trained audiological staff, applying a standard optimized protocol, at the Department of Otorhinolaryngology of the University Hospital Regensburg. Statistical Analysis Used: Mean DPOAE signals were compared between levels by unpaired t test. Novel linear regression models adjusting for other leisure noise exposures and with outcome variables DPoutcome and 4 kilo Hertz (kHz) DPOAEs estimated effects between levels. Results: A total of 1468 subjects (56% female, mostly aged 15 or 16 years) were available for analysis. Comparison of DPOAE means by PMP exposure typically showed no greater than 1 dB difference between groups. In fact, comparisons between ≥90 dB(A) and <80 dB(A) presented the least differences in magnitude. Both DPoutcome and 4 kHz linear regression models presented a weak association with the 4-level PMP exposure variable. An expected dose-response to PMP exposure was not observed in any analyses. Conclusions: DPOAE signal strength alone cannot indicate preclinical NIHL in adolescents.